Bootstrap Inference for Choice-Based Conjoint Analysis - Campana Barbosa, Eduardo; Ribeiro, Alice dos Santos; dos Santos Nascimento, Jhennifer; Gonçalves Batista, Luciano; Henrique Osório Silva, Carlos; Suzana Maria Della Lucia; Paula Rodrigues Minim, Valeria; Andrade de Oliveira, Kamila; César Emiliano, Paulo; Pereira Belo, Lucas (Sigmae, 2024)
This article aims to present an application of Choice-Based Conjoint Analysis (CBCA) with additional inferences for the Choice Probabilities of each treatment and for the Choice Ratios, made through their empirical distributions obtained via bootstrap. This study involved three attributes and eight treatments (light strawberry-flavored yogurt) in a full factorial design. By accessing the empirical distribution of the probabilities and choice ratios, it was possible to make inferences about such quantities, something that is not trivial in the frequentist context. Additionally, bias and standard error values were obtained for the Choice Probabilities and Choice Ratios, making it possible to assess the precision of these estimates, build confidence intervals, and conduct statistical comparisons on these.